2016
DOI: 10.1364/oe.24.024719
|View full text |Cite
|
Sign up to set email alerts
|

Single-view phase retrieval of an extended sample by exploiting edge detection and sparsity

Abstract: We propose a new approach to robustly retrieve the exit wave of an extended sample from its coherent diffraction pattern by exploiting sparsity of the sample's edges. This approach enables imaging of an extended sample with a single view, without ptychography. We introduce nonlinear optimization methods that promote sparsity, and we derive update rules to robustly recover the sample's exit wave. We test these methods on simulated samples by varying the sparsity of the edge-detected representation of the exit w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This speedup makes incorporating dislocation identification into existing phase retrieval algorithms feasible. It could be used to perform the transformation to the dislocation basis, which tends to be sparse [24]. Sparsity using the dislocation basis could be used to circumvent traditional constraints in BCDI, ptychography, and other methods that rely on phase retrieval.…”
Section: Return the Least Entry Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…This speedup makes incorporating dislocation identification into existing phase retrieval algorithms feasible. It could be used to perform the transformation to the dislocation basis, which tends to be sparse [24]. Sparsity using the dislocation basis could be used to circumvent traditional constraints in BCDI, ptychography, and other methods that rely on phase retrieval.…”
Section: Return the Least Entry Of Amentioning
confidence: 99%
“…While these studies have shown great promise, the breadth of 3D BCDI dislocation dynamics measurements and techniques could expand substantially if accurate, robust, and rapid methods existed to determine the 3D dislocation line structure. For example, the datasets generated at diffraction-limited storage rings will likely be too large for existing derivative-based and human-in-the-loop-based methods [23], and the "dislocation basis" could potentially be used as a sparse basis to circumvent constraints in phase retrieval [24]. Here we present such a method by reformulating the dislocation core identification problem as a min-max optimization problem that can be solved rapidly.…”
mentioning
confidence: 99%
“…It has been observed that the ER/HIO/Shrinkwrap combination can aggressively shrink the crystal volume and become trapped in a local minimum that prevents convergence to the true solution 17 . This is because Shrinkwrap is effectively a sparsity promoting operation 44 . The Max Volume metric is designed to favor “anti-sparsity” directly by choosing the largest crystal, which is defined as the crystal with the most nonzero pixels after thresholding the density at 20% of its maximum.…”
Section: Introductionmentioning
confidence: 99%